PENERAPAN KONSEP PEWARNAAN GRAF DALAM PENYUSUNAN JADWAL PELAJARAN MENGGUNAKAN ALGORITMA RECURSIVE LARGEST FIRST DI SMAN 1 AIKMEL TAHUN AJARAN 2024/2025 - Rahim, Meiliza Erfa; Amrullah; Tabita Wahyu Triutami; Sudi Prayitno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem of scheduling teaching and learning activities is a problem that occurs at SMAN 1 Aikmel. The problem is that there are several teachers teaching two different subjects at the same time in different classes. This problem will be solved by applying the concept of graph coloring using an algorithm Recursive Largest First. This article presents the application of the concept of graph coloring in preparing a schedule for teaching and learning activities at SMAN 1 Aikmel. Based on the scheduling data, the adjacency matrix of the scheduling graph is obtained. By using an algorithm Recursive Largest First The chromatic number is 3. Apart from that, it is also found that the maximum number of nodes in one color is 23 nodes. This shows that schedules can be made without overlap at SMAN 1 Ailkmel which has 23 rooms.